The Efficacy of Using Combination Therapy against Multi-Drug and Extensively Drug-Resistant Pseudomonas aeruginosa in Clinical Settings - Frank Jones; Yanmin Hu; Anthony Coates (MDPI AG, 2022)
Pseudomonas aeruginosa is a Gram-negative bacterium which is capable of developing a high level of antibiotic resistance. It has been placed on the WHO's critical priority pathogen list and it is commonly found in ventilator-associated pneumonia infections, blood stream infections and other largely hospital-acquired illnesses. These infections are difficult to effectively treat due to their increasing antibiotic resistance and as such patients are often treated with antibiotic combination regimens. Methods: We conducted a systematic search with screening criteria using the Ovid search engine and the Embase, Ovid Medline, and APA PsycInfo databases. Results: It was found that in many cases the combination therapies were able to match or outperform the monotherapies and none performed noticeably worse than the monotherapies. However, the clinical studies were mostly small, only a few were prospective randomized clinical trials and statistical significance was lacking. Conclusions: It was concluded that combination therapies have a place in the treatment of these highly resistant bacteria and, in some cases, there is some evidence to suggest that they provide a more effective treatment than monotherapies.